1993
DOI: 10.1139/g93-090
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype, C-banding, and Ag-NOR analysis in Diplodus bellottii (Sparidae, Perciforms). Intra-individual polymorphism involving heterochromatic regions

Abstract: A karyotype analysis was carried out in nine specimens of the Sparid species Diplodus bellottii using conventional staining, as well as C-banding and Ag-NOR banding techniques, showing, respectively, 2n = 46 and fundamental number (FN) = 54, and scarce heterochromatic areas irregularly distributed and up to four NOR active regions that were C positive. When compared with the karyotypes of other related species, one centric fusion giving rise to a large metacentric pair and several pericentric inversions seem t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…It shows that the most common chromosome number in the group is 2n = 48 telocentric elements, a condition considered as ancestral for teleosts (Gold, 1979;Ohno, 1974;Vitturi et al, 1995). Assuming that the primitive karyotype for actual teleosteans derives from an ancestral diploid number of 48 telocentric chromosomes, the evolution of the karyotype of Halobatrachus didactylus can be interpreted as the result of at least the central fusion of two pairs of uniarmed chromosomes to form large metacentric or submetacentric elements, resulting in the reduction of the diploid number from 48 to 46, as well as a series of pericentric inversions, translocations and/or simple heterochromatin additions giving rise to the 20 biarmed chromosomes during the species evolution It has been argued that any real difference in the FN between closely related species can be explained as the result of pericentric inversions, whereas the differences in the diploid number (2n) presumably represent Robertsonian changes (fusions, fissions) (LeGrande, 1981;López et al, 1988;Amores et al, 1993); therefore, the FN could be used as an indicator of the accumulation of chromosome reorganisations. The fundamental number (FN) is a common descriptor of the number of chromosome arms, but the methods for calculating it vary among different reports.…”
Section: Resultsmentioning
confidence: 99%
“…It shows that the most common chromosome number in the group is 2n = 48 telocentric elements, a condition considered as ancestral for teleosts (Gold, 1979;Ohno, 1974;Vitturi et al, 1995). Assuming that the primitive karyotype for actual teleosteans derives from an ancestral diploid number of 48 telocentric chromosomes, the evolution of the karyotype of Halobatrachus didactylus can be interpreted as the result of at least the central fusion of two pairs of uniarmed chromosomes to form large metacentric or submetacentric elements, resulting in the reduction of the diploid number from 48 to 46, as well as a series of pericentric inversions, translocations and/or simple heterochromatin additions giving rise to the 20 biarmed chromosomes during the species evolution It has been argued that any real difference in the FN between closely related species can be explained as the result of pericentric inversions, whereas the differences in the diploid number (2n) presumably represent Robertsonian changes (fusions, fissions) (LeGrande, 1981;López et al, 1988;Amores et al, 1993); therefore, the FN could be used as an indicator of the accumulation of chromosome reorganisations. The fundamental number (FN) is a common descriptor of the number of chromosome arms, but the methods for calculating it vary among different reports.…”
Section: Resultsmentioning
confidence: 99%
“…Cases of heterochromatin polymorphism might range from subtle to hypervariable in fish. They can be related to the size of the heterochromatic blocks (Martinez et al, 1991;Jankun et al, 1998) or to associations between heterochromatin and NORs (Hartley, 1988;Amores et al, 1993). Some groups, particularly the Characiformes, present a remarkable karyotype variability influenced by heterochromatinization processes, as extensively seen in the species complex Astyanax scabripinnis (Souza et al, 1996;Mantovani et al, 2000;Mantovani et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, species bearing a single NOR (e.g., A. probatocephalus) or multiple NORs (Diplodus bellottii; Amores et al, 1993;D. puntazzo;Vitturi et al, 1996) have been identified (Table 2).…”
Section: Discussionmentioning
confidence: 99%